Can semipermeable membranes coating materials influence in vivo performance for paliperidone tri-layer ascending release osmotic pump tablet: In vitro evaluation and in vivo pharmacokinetics study - Guangjing Li; Yongjun Wang; Hongming Chen; Donglei Leng; Panqin Ma; Yanjie Dong; Lifang Gao; Zhonggui He (Elsevier, 2015)
One purpose of this study was to develop a paliperidone (PAL) tri-layer ascending release push-pull osmotic pump (TA-PPOP) tablet which could meet the needs of clinical applications. And another purpose was to investigate whether different coating materials influenced in vivo performance of TA-PPOP. The ascending release mechanism of this tri-layer delivery system on theory was elaborated. TA-PPOP was prepared by means of coating with cellulose acetate (CA) or ethyl cellulose (EC). Several important influence factors such as different core tablet compositions and different coating solution ingredients involved in the formulation procedure were investigated. The optimization of formulation and process was conducted by comparing different in vitro release behaviors of PAL. In vitro dissolution studies indicated that both the two formulations of different coating materials were able to deliver PAL at an ascending release rate during the whole 24 h test. The in vivo pharmacokinetics study showed that both self-made PPOP tablets with different coating had a good in vitro-in vivo correlation (IVIVC) and were bioequivalent with the brand product, which demonstrated no significant influence of the coating materials on the in vivo release acceleration of TA-PPOP.